(untitled) (Colloquia Comparativa Litterarum, 2025)
The article compares two fiction books by the Romanian author Ana Blandiana and fellow Bulgarian writer Teodora Dimova. As the analysis reveals the books share a lot of similarities in their approach to the “totalitarian experience”. In these literary works, we can see how through the child’s viewpoint the two female writers show different solutions in times of crises and harrowing circumstances. In summary, Blandiana and Dimova demonstrate in a brilliant aesthetic way the endless possibilities of literature to find salvation even in tragic accidents, and an exit from exile.